2004
DOI: 10.1007/s11249-004-8101-1
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behaviors of 52100 Steel in Carbon Dioxide Atmosphere

Abstract: The tribological behavior of 52100 steel in a carbon dioxide (CO 2 ) atmosphere was investigated using a reciprocating ballon-disk tribometer. X-ray photoelectron spectroscopy (XPS) was used to identify the adsorbed surface layers and tribochemical products. We found that CO 2 can substantially reduce friction and wear of the steel. Adsorbed and reacted surface layers containing iron carbonate and/or bicarbonate play an important role in reducing friction. A disk, exposed once to CO 2 atmosphere, also shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Furthermore, due to contamination, the evidence of the carbonate formation is not very clear and may be hindered by other compound formations however it has been shown by other researchers that CO 2 promotes carbonate formation. The XPS results indicate the existence of iron carbonates due to the presence of CO 2 refrigerant, which is in agreement with findings by Wu et al [8], where they showed that formation of carbonates is possible in 52100 Steel. In their study, different pressures of CO 2 were investigated and it was noted that the higher the pressure of CO 2 , the more the iron carbonate formation.…”
Section: Xps Experimental Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, due to contamination, the evidence of the carbonate formation is not very clear and may be hindered by other compound formations however it has been shown by other researchers that CO 2 promotes carbonate formation. The XPS results indicate the existence of iron carbonates due to the presence of CO 2 refrigerant, which is in agreement with findings by Wu et al [8], where they showed that formation of carbonates is possible in 52100 Steel. In their study, different pressures of CO 2 were investigated and it was noted that the higher the pressure of CO 2 , the more the iron carbonate formation.…”
Section: Xps Experimental Analysissupporting
confidence: 92%
“…This surface ''polishing'' effect was generated by mild wear process or burnishing. Based on the optical micrographs depicted in figure 3 and the friction coefficient values for the different cases, it could be ascertained that adhesion is the main wear mechanism in the cases of N 2 , air and R134a environments, while for the O 2 environment the main wear mechanism was oxidation and for the mild burnishing in the case of CO 2 is chemical wear, in agreement with [8]. Based on these results, the wear mechanism in the cases of O 2 and CO 2 environments is different because CO 2 is fully oxidized as it is a common byproduct compound of the oxidation process whereas O 2 , due to its electronegativity forms chemical bonds with most metals.…”
Section: Friction and Wearsupporting
confidence: 71%
See 3 more Smart Citations